Early Murine Cytomegalovirus (MCMV) Infection Induces Liver Natural Killer (NK) Cell Inflammation and Protection Through Macrophage Inflammatory Protein 1α (MIP-1α)–dependent Pathways - Salazar-Mather, Thais P. (The Rockefeller University Press, 1998)
Natural killer (NK) cells mediate defense against early murine cytomegalovirus (MCMV) infections in liver. The chemokine, macrophage inflammatory protein 1α (MIP-1α), can promote inflammatory responses. Our studies evaluated contributions of NK cells to early MCMV-induced liver inflammation and MIP-1α requirements for inflammation and delivery of antiviral defenses. NK cells were shown to be responsible for focal inflammation, and to be induced to migrate at high levels, in MCMV-infected livers. MIP-1α gene expression was elevated at coinciding times, and mice deficient in MIP-1α function were dramatically inhibited in both inflammatory and protective liver responses. The results precisely define MIP-1α–dependent steps required to achieve NK cell inflammation during, and mechanisms promoting defense against, viral infections in tissues.